2021
DOI: 10.1371/journal.pone.0245058
|View full text |Cite
|
Sign up to set email alerts
|

Efficient association mapping from k-mers—An application in finding sex-specific sequences

Abstract: Genome wide association studies (GWAS) attempt to map genotypes to phenotypes in organisms. This is typically performed by genotyping individuals using microarray or by aligning whole genome sequencing reads to a reference genome. Both approaches require knowledge of a reference genome which hinders their application to organisms with no or incomplete reference genomes. This caveat can be removed by using alignment-free association mapping methods based on k-mers from sequencing reads. Here we present an impro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The successful use of this approach was once again demonstrated using the examples of ampicillin resistance in E. coli and for sex‐related sequences in human sex chromosomes. [ 130 ]…”
Section: Early Methods For Ld and Gwasmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful use of this approach was once again demonstrated using the examples of ampicillin resistance in E. coli and for sex‐related sequences in human sex chromosomes. [ 130 ]…”
Section: Early Methods For Ld and Gwasmentioning
confidence: 99%
“…The successful use of this approach was once again demonstrated using the examples of ampicillin resistance in E. coli and for sex-related sequences in human sex chromosomes. [130] k-mers for GWAS in plants. As mentioned earlier, the utility of kmers for GWAS was also demonstrated, when k-mers were used for ∼ 2000 traits in three plant species, namely A. thaliana, tomato and maize.…”
Section: Svs In Plantsmentioning
confidence: 99%
“…One useful pangenomics tool for measuring non-reference variation that is readily applicable to common 2/29 short-read datasets is the k-mer. K-mers are subsequences of length k derived from a larger sequence and they have a long history of use in computer science [Shannon, 1948], genome assembly [Turner et al, 2018], metagenomics [Benoit et al, 2016], and quantitative genetics [Rahman et al, 2018, Voichek and Weigel, 2020, Kim et al, 2020, Mehrab et al, 2021. Recent studies have also demonstrated the utility of k-mers for measuring heterozygosity and genetic differences between individuals (commonly referred to as "dissimilarity" measures, Ondov et al [2016], Vurture et al [2017], Ranallo-Benavidez et al [2020], VanWallendael andAlvarez [2022]).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple tools have been developed to perform k-mer based GWAS (e.g. bugwas 16 , HAWK 17,18 ). k-mers have the primary advantage of not requiring a reference genome, nor genome assembly.…”
Section: Introductionmentioning
confidence: 99%